rút gọn biểu thức P= 3^2010 – 6^2010 + 9^2010 – 12^2010 + 15^2010 – 18^2010 / -1 + 2^2010 – 3^2010 + 4^2010 – 5^2010 + 6^2010

Question

rút gọn biểu thức P= 3^2010 – 6^2010 + 9^2010 – 12^2010 + 15^2010 – 18^2010 / -1 + 2^2010 – 3^2010 + 4^2010 – 5^2010 + 6^2010

in progress 0
Khoii Minh 1 year 2020-11-03T09:37:48+00:00 1 Answers 76 views 0

Answers ( )

    0
    2020-11-03T09:39:17+00:00

    Đáp án:

    Ta có : 

    `P =  (3^{2010 }- 6^{2010 }+ 9^{2010} – 12^{2010 }+ 15^{2010 }- 18^{2010}) / (-1 + 2^{2010} – 3^{2010} + 4^{2010} – 5^{2010 }+ 6^{2010})`

    `= [-3^{2010}.(-1 + 2^{2010} – 3^{2010} + 4^{2010} – 5^{2010 }+ 6^{2010})]/(-1 + 2^{2010} – 3^{2010} + 4^{2010} – 5^{2010 }+ 6^{2010})`

    `= -3^{2010}`

    Giải thích các bước giải:

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )